PENGARUH MODEL NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR PPKN KELAS X SMK N 7 PONTIANAK - Widayatul Akmar; Agus Sastrawan Noor; Rum Rosyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study was conducted using an experimental method in form of pre-experimental with the one-group pretest-posttest design. The subjects in this study were 35 10th-grade students of Multimedia A Class of Vocational High School 7 Pontianak. The instrument used were test questions with 20 multiple choices of test items. The mean scores in pretest and posttest show an increase from 52.47 to 79.28. The data were normally distributed for after the normality test the value of significance (2-tailed) data is greater than alpha 0.05. Based on the results of paired sample t-test, it showed the significance value (2-tailed) 0.00<0.05, hence, Ho was rejected and Ha was accepted. The decision making based on determining the t-table value obtained 8.379>2.0345; consequently, Ho was rejected. Based on the calculation of the effect size, obtained the value of 3.57, categorized as high. Therefore, the Numbered Head Together learning model was effective towards students’ learning outcomes in PKn Subject, especially in the material of Threat to the State in the Frame of Bhinneka Tunggal Ika.Keywords: Learning Model,  Learning Outcomes,  Numbered Head Together,  PPKn